Baltic Cod, Cruise No. AL594, 13 May – 27 May 2023, Kiel (Germany) – Kiel (Germany) - Reusch, Thorsten (GEOMAR Helmholtz Centre for Ocean Research, Research Division Marine Ecology/Marine Evolutionary Ecology, 2024)
The cruise AL594 "Baltic Cod" focused on the status of the Eastern Baltic cod stock, along with its prey fields (zooplankton and pelagic fish prey) and hydrographic boundary conditions. The cruise extended a 38yr long-term data series on (eco-)system composition and functioning of the Baltic Sea, with a focus on the deeper basins. Collaborations included (i) sampling and experimentation on phytoplankton-virus and -grazer interactions (Uni HH, Dr. Luisa Listmann) (ii) cod gonad and liver sampling for fecundity and parasite studies (in collaboration with Dr. Jonna Tomkiewicz, DTU Aqua) (iii) the study of microbially mediated vitamin B1 (thiamine) dynamics in the Baltic Sea along a salinity gradient (Dr. Kristin Bergauer, GEOMAR). The cruise focused on the Bornholm Basin as most important remaining spawning area of Eastern Baltic cod, but also included the Western Baltic Sea (Kiel and Mecklenburg Bight) and the Arkona Basin. Detailed zoo- and ichthyoplankton sampling was conducted in the Western Baltic (Mecklenburg Bight, Arkona Basin) to contribute to spatially resolved recruitment data of Western Baltic cod via the “Winter cod 2021-2025” program in the BMBF-DAM funded Project SpaCeParti. Subsamples of cod (Gadus morhua), whiting, and flatfish species were taken to determine stock structure, gonadal maturation, stomach contents, and egg production (sprat and cod), and to sample tissue and otolith samples for individual-level genomic and ecological analyses (cod). Here, we present the following first results (i) cod nutritional condition is no longer deteriorating, while individual growth rates have significantly decreased in the past 29 years (ii) the size structure of the stock is still not recovering towards larger individuals, with most individuals (>99%) smaller than 50 cm in length and (iii) Eastern Baltic cod shows moreover signs of recent fisheries induced evolution towards reduced growth rates that are mirrored in genomic changes.